Thorough-Bass Accompaniment According to Johann David Heinichen - Buelow, George J. 1929-2009; Heinichen, Johann David 1683-1729 (Lincoln, NB University of Nebraska Press, 1992)
Johann David Heinichen (1683-1729) was a distinguished composer, a contemporary of Johann Sebastian Bach, and Cappellmeister at the court of August I in Dresden. His treatise, Der General-Bass in der Composition, is one of the most comprehensive sources for the late Baroque practice of figured-bass, or thorough-bass, accompaniment. It is a fund of information about many complex problems confronting musicians in the performance and interpretation of Baroque music, including meters, embellishments, dissonance, particular complications for recitative, and use of the figured bass.With a judicious combination of translation, interpretation, and commentary George J. Buelow makes Heinichen's famous treatise accessible for contemporary scholars and performers. Buelow provides translations of key sections of the treatise, explains its historical significance, clarifies Heinichen's obscurities, and relates the treatise to other musical theories and practices of the Baroque, including those of Gasparini, Mattheson, and the Bachs. Buelow, one of the world's premier experts on Baroque music, is a professor of musicology at Indiana University.
Heinichen's treatise was originally published in 1728, see C1.67 03F15
Keywords: Heinichen, Johann David -- 1683-1729; 18th Century (1701-1800); Method; Basso continuo; Accompaniment; Germany